Empathic Accuracy: Worse Recognition by Older Adults and Less Transparency in Older Adult Expressions Compared With Young Adults. (30th January 2019) - Ruffman, Ted; Halberstadt, Jamin; Murray, Janice; Jack, Fiona; Vater, Tina
Abstract: Objectives: We examined empathic accuracy, comparing young versus older perceivers, and young versus older emoters. Empathic accuracy is related to but distinct from emotion recognition because perceiver judgments of emotion are based, not on what an emoter looks to be feeling, but on what an emoter says s/he is actually feeling. Method: Young (≤30 years) and older (≥60 years) adults ("emoters") were unobtrusively videotaped while watching movie clips designed to elicit specific emotional states. The emoter videos were then presented to young and older "perceivers, " who were instructed to infer what the emoters were feeling. Results: As predicted, older perceivers' empathic accuracy was less accurate relative to young perceivers. In addition, the emotions of young emoters were considerably easier to read than those of older emoters. There was also some evidence of an own-age advantage in emotion recognition in that older adults had particular difficulty assessing emotion in young faces. Discussion: These findings have important implications for real-world social adjustment, with older adults experiencing a combination of less emotional transparency and worse understanding of emotional experience.